2008
DOI: 10.4161/cc.7.8.5783
|View full text |Cite
|
Sign up to set email alerts
|

IAPS : More than just inhibitors of apoptosis proteins

Abstract: Inhibitors of apoptosis proteins (IAPs) are a conserved family of proteins identified in species ranging from virus, yeasts, nematodes, fishes, flies and mammals. The common structural feature is the presence of at least one Baculovirus IAP Repeat (BIR) domain. Hence, IAPs are also known as BIR-containing proteins (BIRCs). Most of them display anti-apoptotic properties when overexpressed. In drosophila, IAPs are sufficient and necessary to promote cell survival through a direct regulation of apoptotic protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
170
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(175 citation statements)
references
References 116 publications
(222 reference statements)
3
170
0
2
Order By: Relevance
“…12 The XIAP protein has a central role in the proinflammatory response, leading to activation of NFkB and subsequent activation of proinflammatory cytokines via the NOD signaling pathway, as well as a crucial role in mediating programmed cell death. [13][14][15] Functionally testing these pathways in the patient's cells provided results consistent with aberrant XIAP function: muramyl dipeptide stimulation of patient's PBMCs was unable to induce the expression of IL-8 compared with controls (Fig. 4A), and CD3 stimulation of PBMC blasts resulted in enhanced apoptosis in the patient compared with controls (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…12 The XIAP protein has a central role in the proinflammatory response, leading to activation of NFkB and subsequent activation of proinflammatory cytokines via the NOD signaling pathway, as well as a crucial role in mediating programmed cell death. [13][14][15] Functionally testing these pathways in the patient's cells provided results consistent with aberrant XIAP function: muramyl dipeptide stimulation of patient's PBMCs was unable to induce the expression of IL-8 compared with controls (Fig. 4A), and CD3 stimulation of PBMC blasts resulted in enhanced apoptosis in the patient compared with controls (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…The BIR2 domain of XIAP inhibits caspase-3 and caspase-7, while BIR3 binds to and inhibits caspase-9. The RING domain utilizes E3 ubiquitin ligase activity and enables IAPs to catalyze ubiquitination of self, caspase-3, or caspase-7 (Dubrez-Daloz et al 2008). It has been demonstrated that in the failing human heart, XIAP is downregulated, indicating that the cardiomyocytes were more sensitive to apoptosis (Haider et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Played an Important Role in Anchorage-independent Growth and Cell Cycle G 1 /S Progression of Colon Cancer Cells-It has been verified that XIAP has additional biological functions that do not rely on its inhibition of apoptosis (12,33). To delineate the biological significance of XIAP in cancer cell proliferation, HCT116 XIAP-deficient (XIAPϪ/Ϫ) transfectants with XIAP (HA-XIAP) and XIAP H467A, a point mutation resulting in loss of its E3 ubiquitin ligase activity (34), were seeded in soft agar for determination of its anchorage-independent growth capability compared with WT(vector) and XIAPϪ/Ϫ(vector).…”
Section: Xiap and Its E3 Ligasementioning
confidence: 99%